Structure and Properties of Boride Coatings Obtained by the Plasma-Arc Method - Nguyen Van Vinh; Nguyen Van Trieu; Andrey Evgenievich Balanovskiy; Astafieva Natalia Anatolievna (Tribology in Industry, 2023)
An important problem of modern materials science is to increase the strength and wear resistance of tools and various machine parts. Boriding is one of the promising methods for increasing the surface hardness and wear resistance, resistance to oxidation and corrosion of machine building parts. In this work, boride coatings were obtained using plasma doping technology. It has been established that with an increase in current strength from 120 A to 160 A, the microstructure changes from hypereutectic to hypoeutectic. The maximum hardness was recorded on the sample surface with a current of 120 A and is 1519 HV. After the sliding friction test, it was noted that the boride coating at a current of 120 A has the highest wear resistance.